Tiktok Live Stream Shopping Information: Consumer Purchase Behavior in Gen Z - Fransiska, Putu Ika; Ida Ayu Oka (GoAcademica Research & Publishing, 2023)
This study aims to influence the quality of information and the credibility of information on purchase intentions with hedonic experience and the use of information as a mediator and affordability of interactivity as a moderator. The population of this study were all TikTok social media users whose exact number is unknown because it always changes every time, with a sample size of 115. Data collection was carried out by distributing questionnaires using the Google form. The data analysis technique used is SEM-PLS. The results of this study indicate that the quality of information, hedonic experience, the usefulness of information has a positive and significant effect on purchase intention. Information credibility has no significant effect on purchase intention. Information quality, information credibility has a positive and significant effect on hedonic experience. The quality of the information has no significant effect on the usefulness of the information. Information credibility has a positive and significant effect on the usefulness of information. Information quality and information credibility have a positive effect on purchase intention with hedonic experience as a mediator. Information quality, information credibility has a positive effect on purchase intention with the use of information as a mediator. Interactivity affordability is not able to moderate the effect of information quality and information credibility on purchase intention.